Introduction to electric circuits - Dorf, Richard C. (Wiley, 1996)
From space station photo cells to superconducting electromagnets to electric shark control fences, readers see first hand how the material in this book relates to actual problems faced by engineers today. This brings the subject to life like no other book!. The central theme of this bestselling textbook is that electronic circuits are part of the basic fabric of modern technology. Demonstrates how the analysis and design of these circuits are inseparably intertwined with the engineer's ability to design complex electronic, communication, computer and control systems as well as consumer products. A major effort has been made to provide the history and the current motivation for each of the topics discussed.